PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VII.A SMP NEGERI 1 SIAK HULU - Tiara Rubiandar; Yenita Roza; Putri Yuanita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to improve the learning process and the student’s mathematical problem solving skill by applying Problem Based Learning (PBL) model. This type of research is classroom action research with two cycles. This research was conducted in collaboration between researcher and teacher of mathematics. Subjects were students of class VII.A SMP Negeri 1 Siak Hulu. Study was conducted in the first semester of academic year 2018/2019. The research instrument consists of mathematical learning instruments and instruments to collect data. Mathematical learning instruments used in this study are syllabus, lesson plans, and activity sheets. Data collection instruments used in this study is observation sheets and mathematical problem solving tests. Data analysis technique in this study is analysis descriptive narrative of qualitative data and descriptive statistical analysis of quantitative data. The result of this study showed that the implementation of PBL improved the learning process and the student’s mathematical problem solving skill. The student’s average value in cycle I which is 59,48 had improved to 86,00 in cycle II. The improvement also found in the indicator average value in identifying the problem, devising a plan to solve the problem, carrying out the plan to solve the problem, and interpreting the solution. This study concludes that the implementation of PBL improved the learning process and the student’s mathematical problem solving skill at class VII.A SMP Negeri 1 Siak Hulu. PBL model can be used as an alternative to learning, because through this learning can improve the learning process and mathematical problem solving skill of the students.Key Words: Problem Based Learning, Mathematical Problem Solving Skill, Learning Process.